2022
DOI: 10.3390/insects13121156
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Aspects of the Phlebotominae Fauna (Diptera: Psychodidae) among Forest Fragments and Built Areas in an Endemic Area of American Visceral Leishmaniasis in João Pessoa, Paraíba, Brazil

Abstract: Sand flies are dipterans of medical importance, as some species are vectors of American visceral leishmaniasis (AVL). The municipality of João Pessoa (Paraíba, northeastern Brazil), is an endemic region for AVL, having high rates of human and canine cases. The main objective was to evaluate the sand fly fauna among forest fragments and built areas, and its relationship with environmental conditions. HP light traps were placed in the studied areas from March 2019 to July 2021. A total of 2141 specimens of phleb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
1
0
0
Order By: Relevance
“…(Silveira et al, 2012). Besides our study, other researchers (Trüeb et al, 2018;Silva et al, 2022) have shown that urbanized areas present differences in sandfly richness and diversity compared to forest fragments, and have concluded that the conservation of forest areas, even as fragments in urban areas, favors the diversity of phlebotomine species. As has been done in several other Brazilian cities, this study uses clinical and laboratory findings to confirm the presence of autochthonous cases of canine visceral leishmaniasis in an urban area in the city of Belém.…”
Section: Discussionsupporting
confidence: 68%
“…(Silveira et al, 2012). Besides our study, other researchers (Trüeb et al, 2018;Silva et al, 2022) have shown that urbanized areas present differences in sandfly richness and diversity compared to forest fragments, and have concluded that the conservation of forest areas, even as fragments in urban areas, favors the diversity of phlebotomine species. As has been done in several other Brazilian cities, this study uses clinical and laboratory findings to confirm the presence of autochthonous cases of canine visceral leishmaniasis in an urban area in the city of Belém.…”
Section: Discussionsupporting
confidence: 68%